2020
DOI: 10.1002/hpm.2979
|View full text |Cite
|
Sign up to set email alerts
|

Regional health disparities in Burkina Faso during the period of health care decentralization. Results of a macro‐level analysis

Abstract: Summary Background Burkina Faso has undertaken decentralization reforms in the health care sector to improve the performance of the health system. This study aimed to analyze the differences in health outcomes by health district's demographic and economic status, and the distribution of health resources during the period of health care decentralization. Methods A bivariate correlation analysis was conducted using data at the health districts and regions lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Healthcare decentralisation has been most used in Africa, where it is notably diffused in the countries of the sub-Saharan region, such as Ghana, 30 Kenya 31 and Burkina Faso. 32 However, we observe a lack of studies concerning the adoption of health decentralisation in the MENA area, despite there being a programme in Tunisia to apply decentralisation, especially in the healthcare sector. Thus, an information gap emerges which needs to be filled.…”
Section: The Theoretical Background Of the Healthcare System Decentra...mentioning
confidence: 89%
“…Healthcare decentralisation has been most used in Africa, where it is notably diffused in the countries of the sub-Saharan region, such as Ghana, 30 Kenya 31 and Burkina Faso. 32 However, we observe a lack of studies concerning the adoption of health decentralisation in the MENA area, despite there being a programme in Tunisia to apply decentralisation, especially in the healthcare sector. Thus, an information gap emerges which needs to be filled.…”
Section: The Theoretical Background Of the Healthcare System Decentra...mentioning
confidence: 89%
“…Bronze medals were more frequent in the Northern and Eastern districts of Burkina Faso, while Western Districts had a majority of silver and gold medals. In addition to differences in the quality of anthropometric and vital signs measures, this geographical heterogeneity could also reflect variations in socioeconomic and nutritional status across the country (17,18). Previous reports showed that food insecurity is the most prevalent in the Sahel (Northern) and East regions.…”
Section: Discussionmentioning
confidence: 99%
“…In Burkina Faso for instance the ratio of health infrastructure and of clinic visits per capita is estimated to be 1.03 (range 0.11–2.03) per 10,000 and 0.6 (range 0.08–1.01) per person per year respectively. Most deprived populations live in rural and remote settings [ 34 ]. Microplanning using satellite imagery and other geographic information systems [ 13 , 15 ] are emerging strategies in door-to-door delivery and likely has recently contributed to wild polio eradication from Africa [ 35 ].…”
Section: Discussionmentioning
confidence: 99%